Effects of High-Definition Anodal Transcranial Direct Current Stimulation Applied Simultaneously to Both Primary Motor Cortices on Bimanual Sensorimotor Performance - Pixa, Nils H.; Steinberg, Fabian; Doppelmayr, Michael (Frontiers in Behavioral Neuroscience, 2017)
Many daily activities, such as tying one’s shoe laces, opening a jar of jam or performing a free throw in basketball, require the skillful coordinated use of both hands. Even though the non-invasive method of transcranial direct current stimulation (tDCS) has been repeatedly shown to improve unimanual motor performance, little is known about its effects on bimanual motor performance. More knowledge about how tDCS may improve bimanual behavior would be relevant to motor recovery, e.g. in persons with bilateral impairment of hand function. We therefore examined the impact of high-definition anodal transcranial direct current stimulation (HD-atDCS) on the performance of a bimanual sequential sensorimotor task. Thirty-two volunteers (age M=24.25; SD=2.75; 14 females) participated in this double-blind study and performed sport stacking in six experimental sessions. In sport stacking, twelve specially designed cups must be stacked (stacked up) and dismantled (stacked down) in predefined patterns as fast as possible. During a pretest, posttest, and follow-up test, two sport stacking formations (3-6-3 stack & 1-10-1 stack) were performed. Between the pretest and posttest, all participants were trained in sport stacking with concurrent brain stimulation for three consecutive days. The experimental group (STIM-M1) received HD-atDCS over both primary motor cortices (M1), while the control group received a sham stimulation (SHAM). Three-way ANOVA revealed a significant main effect of TIME and a significant interaction of TIME x GROUP. No significant effects were found for GROUP, nor for the three-way interaction of TIME x GROUP x FORMATION. Further two-way ANOVAs showed a significant main effect of TIME and a non-significant main effect for GROUP in both sport stacking formations. A significant interaction between TIME x GROUP was found only for the 3-6-3 formation, indicating superior performance gains for the experimental group (STIM-M1). To account and control for baseline influences on the outcome measurements, ANCOVAs treating pretest scores as covariates revealed a significant effect of the stimulation. From this, we conclude that bilateral HD-atDCS over both primary motor cortices improves motor performance in a bimanual sequential sensorimotor task. These results may indicate a beneficial use of tDCS for learning and recovery of bimanual motor skills.